Coyote Hills : a novel - Kellerman, Jonathan; Kellerman, Jesse (Clay Edison series, 2025)
Clay Edison has left behind the Alameda County coroner's office to strike out on his own as a private investigator. He's perfectly happy working low-stakes embezzlement cases--that is, until PI Regina Klein calls him with a mystery only he can solve. The son of a wealthy couple has washed up dead on the shores of San Francisco Bay with a head injury and drugs in his system. The police are calling it an accident. But the parents are adamant something's not right--and as Clay digs deeper, he uncovers a horrifying tangle of betrayal and lies.